A Speech Act Analysis of the Utterances of Selected Key Actors in the Russian/Ukrainian Crisis: Pragmatics - FAFIYEBI, Damilola Oluseyi; Fafiyebi, Oluwabusayo Foluso (International Journal of Language and Literary Studies, 2025)
The interconnection between language and conflict is one that has continued to attract the attention of scholars all over the world. This is not unconnected with the role of language both as an instrument of ensuring peace and for causing crisis. The current research seeks to examine language as employed by state actors in the ongoing crisis between Russia and Ukraine. The research is targeted at finding out how language is used in conveying action even in times of conflict. As a pragmatic explication, the study seeks to examine how meaning is derived from language in conflict situation. The research employs the speech act theory as its analytical tool so as to provide a solid theoretical base for the study. It is also that the study will shed light on the effect of context on the language choices employed in the data selected for the study. The research identifies the various linguistic actions performed in the selected data as being at least one of assertive, commissives, declaratives, expressives and directives. The study shows that the majority of the statements employed by each of these two perform the act of condemning. Criticizing, encouraging and soliciting. The speakers employ these notable strategies to achieve different communicative intentions that are designed to further the aim of the communicative goal. The goal of condemning is achieved through the strategy of positive self-presentation and negative presentation of others.